THE RELATIONSHIP BETWEEN AUTONOMY AND WORK ENGAGEMENT AMONG LECTURERS AT KAJANG VOCATIONAL COLLEGE - Ibrahim, Nurul Nabila Binti; Mohd Yahaya, Evva Kumala Binti (Selangor Humaniora Review, 2024)
Providing employees with more autonomy at work has increased their work engagement. However, past research did not highlight how autonomy can enhance work engagement in the context of vocational college lecturers. It is essential to perform studies in this area because vocational college lecturers are demanded with quality competency to deliver significant practical knowledge. In this investigation, a quantitative research strategy was used. The data was gathered using a series of questionnaires that included the 9-item Work Design Questionnaire (WDQ) scale and the Utrecht Work Engagement Scale (UWES-9) for the 9-item scale. The study found that when people have more control over their work and can make decisions that match their values, they feel more energized, committed, and focused on their tasks. This sense of control leads to a strong feeling of ownership and responsibility for the results of their work.